The symphony of Scripture making sence of the Bible's many themes - Strom, Mark, 1956- (Phillipsburg, NJ Presbyterian and Reformed, 2001)
Includes bibliographical references and indexes.
Originally published : Downers Grove, IL. : IVP, c. 1990
Keywords: BIble -- criticism, interpretation, etc